Socio-economic aspects of Abet farming households - Ingawa, S.A. (International Livestock Centre for Africa, 1986)
Reports findings from a socio-economic survey of farming households in Abet area in subhumid Nigeria concentrating on allocation of household & non-household labour during the year & its allocation among the various crops grown in the area, sources & amounts of income and patterns of expenditure.